Indigenous Substitutes for "Lignum Vitae" for Making Stern Bearings for Fishing Boats - VELD, M.; SIVADAS, T. K. (Fishery Technology, 2025)
Difficulties are very often encountered in selecting proper material for making stern bearings for fishing boats. Conventional materials such as white metal, bronze etc. wear out too fast also causing considerable wear to the propeller shaft. Lignumvitae, a natural wood commonly used for this purpose, is not available on a commercial scale in our country. Results of trials carried out to find out suitable substitutes for lignum-vitae from among indigenous timbers are presented in this paper.